Bulk and nano‐mechanical behavior of silver and silver‐CNT‐reinforced hybrid polymer composites. Issue 8 (12th April 2015) - Chakraborty, Himel; Ray, Dipa; Chattopadhyay, Partha Protim
Abstract : The present study concerns study of the Bulk and nano‐mechanical properties of Ag‐CNT vis‐à‐vis Ag reinforced polymer composites. The Ag‐CNT hybrid powder blend was prepared by mechanical milling. Variation of the bulk and nano‐mechanical properties has been attributed to the morphological features and the degree of dispersion of the fillers. It has been found that dispersion of Ag‐CNT hybrid particle is beneficial for improvement of both the mechanical properties. POLYM. COMPOS., 37:2581–2587, 2016. © 2015 Society of Plastics Engineers